Leaving Group Assisted Strategy for Photoinduced Fluoroalkylations Using N‐Hydroxybenzimidoyl Chloride Esters. (5th December 2018) - Zhang, Weigang; Zou, Zhenlei; Wang, Yuanheng; Wang, Yi; Liang, Yong; Wu, Zhengguang; Zheng, Youxuan; Pan, Yi
Abstract: Redox‐active esters (RAEs) as alkyl radical precursors have been extensively developed for C−C bond formations. However, the analogous transformations of fluoroalkyl radicals from the corresponding acid or ester precursors remain challenging because of the high oxidation potential of the fluoroalkyl carboxylate anions. The newly developed N ‐hydroxybenzimidoylchloride (NHBC) ester provides a general leaving group assisted strategy to generate a portfolio of fluoroalkyl radicals, and can be successfully applied in photoinduced decarboxylative hydrofluoroalkylation and heteroarylation of unactivated olefins. In addition, DFT calculations revealed that the NHBC ester proceeds by the fluorocarbon radical pathway, whereas other well‐known RAEs proceed by the nitrogen radical pathway.